Management Statement on the Temporary Suspension of Implementing the Policy for Country Contributions for Capacity Building. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This statement provides an update on the implementation of the strengthened country contributions policy for capacity building (the "Policy") and informs the Executive Board of management's intention to suspend temporarily implementation of the Policy. As noted in the Statement of the General Counsel of July 23, 2008, management has the authority to establish and to implement changes to the Policy, in consultation with the Executive Board.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet